Herbal medicines from the industry in the unified health system: challenge faced by medical professionals - Caroline Gribner; Paula Francislaine Moura; Ana Angélica Ruscheweyh Rigoni; Mirna Clemente; Yanna Dantas Rattmann; Eliane Carneiro Gomes (Universidade de São Paulo, 2023)
Abstract The World Health Organization recognized the use of herbal medicines as a therapeutic resource and its application in the primary attention to heath. The begin of this expansion was in 2006, with the National Policy on Integrative and Complementary practices of the Unified Health System (SUS). This research aimed to evaluate the questionnaires applied to doctors, who may have prescribed industrialized herbal medicines and to identify the difficulties involved with the implementation of this therapy as an integrative and complementary practice. It is a quantitative, observational and transversal study conducted in the municipality of Pinhais/Brazil. The questionnaire applied had as themes the experience of personal use of industrialized herbal medicines, improvement after their use. Forty-four individuals from four different nationalities: Brazilian (88.64%), Cuban (6.82%), Mexican (2.27%) and Argentinian (2.27%), ages between 25 and 69 years, mainly male sex (54.55%) answered the questionnaire. According to the study, the doctors consider herbal medicines an alternative to the conventional treatment and these medical professionals have already prescribed some industrialized herbal medications. Despite the difficulties faced by medical doctors with the prescription of herbs, it is possible to define strategies to assist these professionals, such as the incentive the actions by the governments.